Evaluation of a Sample of Patients With Unilateral Cleft Lip and Palate Treated With a Two-Stage Protocol. Issue 8 (November 2018) - Brusati, Roberto; Meazzini, Maria Costanza; Rezzonico, Angela; Biglioli, Federico; Garattini, Giovanna; Battista, Valeria Marinella Augusta; Autelitano, Luca
Abstract : Abstract: The aim of this paper was to assess growth, speech, and aesthetic results at the completion of growth in patients with unilateral cleft lip and palate treated with the 2 stages Milan surgical protocol. Craniofacial growth was evaluated with cephalometric analysis and a theoretical need for orthognathic surgery. Nasolabial appearance was qualitatively assessed using the Asher McDade Aesthetic Index. Speech was assessed using the Gos.Sp.Ass '98 modified for Italian language scoring system. Burden of care was recorded in terms of number of secondary surgical procedures. All of the patients were treated and evaluated at San Paolo Hospital, Smile House, Milan. Fifty-two consecutive patients treated by the same surgeon were recalled, 12 patients did not come for assessment. The first surgical step (average age of 6 months) was cheilorhinoplasty (Millard modified Delaire technique) and soft palate rapair (Pigott). The second step (average age of 35 months) was hard palate and alveolar repair performed simultaneously with an early secondary gengivo alveolo plasty. Fifty-six percent of the patients did not need further surgery after the 2-stage surgery protocol. The 2-stage surgical protocol of Milano, Smile House, seems to be effective for treatment of unilateral cleft lip and palate, with good results in terms of speech, labial appearance, and alveolar cleft management. Nevertheless, maxillary growth was moderately impaired by the protocol.